Editorial: The ongoing challenges - David Robie (Asia Pacific Network, 2010)
The notion that the war correspondents of today are essentially the same as their colleagues of, say the Vietnam war of more than four decades ago—but now armed with laptops, satellite dishes and digital cameras—is a fallacy. Australian author and media educator Tony Maniaty reminds us thus in this edition of Pacific Journalism Review. He writes: